Call to Action: Prevention of Mother-to-Child Transmission of Hepatitis B in Africa. (17th January 2018) - Wilson, Peyton; Parr, Jonathan B; Jhaveri, Ravi; Meshnick, Steve R
Abstract: Hepatitis B virus (HBV) is a significant public health issue that has not been adequately addressed, especially in the high-prevalence region of Africa. Despite the incorporation of HBV vaccines into the Expanded Program on Immunization, children continue to be infected with HBV through maternal-to-child transmission (MTCT). The addition of a birth dose of HBV vaccine would be a cost-effective method to reduce MTCT. Birth-dose HBV vaccine policies have been adopted in the Western Pacific region but not yet in Africa. Even better protection against HBV MTCT can be achieved by treatment of pregnant women with high HBV viral loads with tenofovir. Tenofovir is already widely used in prevention of HIV MTCT (PMTCT) programs. We suggest that existing HIV PMTCT programs could be expanded to deliver care for HBV-infected pregnant women. With appropriate adoption of birth-dose vaccination policies and expansion of PMTCT programs, elimination of HBV MTCT in Africa is achievable.